(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In today’s world, where social media, videos, and digital content are everywhere, teaching foreign languages needs to go beyond just grammar and vocabulary. Students learning a new language should also know how to navigate and critically understand media in that language. This article dives into how we can weave media literacy into foreign language education at the university level. We’ll look at what teaching methods work, the hurdles instructors face, and the benefits students gain. Using a mix of surveys and a hands-on classroom experiment with English as a Foreign Language (EFL) students, this study shows that media literacy can make learning more engaging, sharpen critical thinking, and spark creativity. But it’s not all smooth sailing—challenges like limited teacher training, lack of resources, and institutional gaps can make things tricky. The takeaway? Schools need better training, resources, and curriculum updates to make this work.